AUDIT REPORT LAG IN BANKING COMPANIES: AN INDONESIAN EVIDANCE - Made Christin Dwitrayani; Putu Mega Juli Semara Putra; I Made Sudiartana; Ni Made Rai Juniariani (KRISNA: Kumpulan Riset Akuntansi, 2025)
The information contained in a company's financial reports can be useful if it is presented accurately and on time when needed by users of financial reports such as creditors, investors, auditors, government, society, and other parties as a basis for making decisions. The inaccuracy of the audit report (audit report lag) will have an impact on the company's credibility. Timeliness in completing a financial report audit is seen from the date of the company's financial report to the date of the independent auditor's report. This research was conducted to deetermine the effect of profitability, solvency, company size, auditor reputation, and audit opinion on audit report lag in banking companies listed on the Indonesia Stock Exchange in 2020-2022. The population in this research is 47 banking companies registered on the IDX in 2020-2022. The sample in this research was 4 companies determined based on the purposive sampling method. The analysis technique used in this research is multiple linear regression analysis. The results of this research show that the variables profitability, company size, and auditor reputation have a negative effect on audit report lag, while solvency and audit opinion do not affect audit report lag in banking companies listed on the Indonesia Stock Exchange in 2020-2022.